2020
DOI: 10.1007/s11628-020-00413-w
|View full text |Cite
|
Sign up to set email alerts
|

Overcompensation as a service recovery strategy: the financial aspect of customers’ extra effort

Abstract: Compensation is one of the most important elements of service. Companies often pursue a strategy of overcompensation; however, there are contradictory results in the literature whether overcompensation has a positive or negative effect on postcomplaint customer behaviour. In this paper, based on three studies, we prove that examining the amount of additional effort required of the customer in order to achieve service recovery can help us better explain outcomes of the service recovery. Our results clearly show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
1
2
0
2
Order By: Relevance
“…This finding is comparable with the results of a study by Stakhovych and Tamaddoni (2020) who similarly found that service recovery was negatively affected by PSSF. Moreover, our findings agree with those by Kenesei and Bali (2020), who found that the bigger the severity of service failure was conceived, the less SRS was successful. Evidence from this study showed that PSSF had positively influenced customer NWoM regardless of airline carrier.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is comparable with the results of a study by Stakhovych and Tamaddoni (2020) who similarly found that service recovery was negatively affected by PSSF. Moreover, our findings agree with those by Kenesei and Bali (2020), who found that the bigger the severity of service failure was conceived, the less SRS was successful. Evidence from this study showed that PSSF had positively influenced customer NWoM regardless of airline carrier.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…However, as Stakhovych and Tamaddoni (2020) noted, the severity of the service failure, as perceived by the customer, can have a dramatic impact on the effectiveness of any SRS that the transgressing firm might use. Similarly, Kenesei and Bali (2020) found that SRSs were less effective when the severity of the service failure was perceived as more intense. Therefore, the following hypothesis was proposed: H1.…”
Section: Perceived Severity Of Service Failurementioning
confidence: 89%
“…Finally, in terms of saturation, we followed Glaser and Strauss’s ( 1967 , p. 61) approach in grounded theory that focuses on theoretical saturation: as the interviews and their concurrent analysis progressed, categories started to repeat themselves despite our efforts to ensure diversity among interviewees (e.g., how consumers described their playing habits and what kind of games practitioners were involved with) (see also Kenesei and Bali 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…‫منافسة‬ ‫شركات‬ ‫إلى‬ ‫تحولهم‬ ‫وتجنب‬ ‫عمالئها‬ ‫إلرضاء‬ ‫للشركات‬ ‫أخيرة‬ (Kenesei & Bali, 2020). (Bearden et al, 1998;Nel et al, 2000;Zhu et al,…”
Section: ‫وبالتا‬ ‫وفرصة‬ ‫للعميل‬ ‫الشركة‬ ‫تقدمها‬ ‫إضافية‬ ‫وخدمة‬...unclassified
“…‫أخيره‬ ‫وفرصة‬ ‫للعميل‬ ‫الشركة‬ ‫تقدمها‬ ‫إضافية‬ ‫وخدمة‬ ‫تحدى‬ ‫بمثابة‬ ‫الخدمة‬ ‫إصالح‬ ‫ويعتبر‬ ‫منافسة‬ ‫شركات‬ ‫إلى‬ ‫تحولهم‬ ‫وتجنب‬ ‫عمالئها‬ ‫إلرضاء‬ ‫للشركات‬(Kenesei & Bali, 2020) ‫وتشير‬ .…”
unclassified